MODEL PEMBELAJARAN KONSTRUKTIVISME UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP - Taufiq (Numeracy, 2018)
This research is an experimental study in SMP Negeri 1 Sigli with pretest and posttest research design given to the experimental group and the control group. The experimental group learns through constructivism learning models and learning control groups through ordinary learning. While the instrument used is a test of mathematical communication skills and student attitude scale. The subject of the study were students of SMP Negeri 1 Sigli in Pidie Regency, with the sample subjects being students of class VIII-A as the experimental group and students of class VIII-B as the control group. The main objective of this research is to examine the mathematical communication skills of junior high school students who learn with constructivism learning in small groups and those who study normally, the relationship between these two abilities and students' attitudes toward learning with constructivism learning models. Data analysis is carried out quantitatively and qualitatively. Quantitative analysis was carried out on the pretest and posttest data, to see the average difference between the two sample groups. Based on the results of the final test analysis, it was found that students' mathematical communication skills who learned with constructivism learning model were better than students who learned with ordinary learning. Student learning outcomes in the experimental group are at a good level and the control group learning outcomes are still at a less level. While the qualitative analysis found that the learning activities of students in constructivism learning models in small groups are good. Students and teachers show a positive attitude towards this learning. Abstrak Penelitian ini merupakan studi eksperimen di SMP Negeri 1 Sigli dengan desain penelitian pretes dan postes yang diberikan pada kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen belajar melalui model pembelajaran konstruktivisme dan kelompok kontrol belajar melalui pembelajaran biasa. Sedangkan instrumen yang digunakan adalah tes kemampuan komunikasi matematik dan skala sikap siswa. Subjek penelitian adalah siswa SMP Negeri 1 Sigli di Kabupaten Pidie, dengan subjek sampel adalah siswa kelas VIII-A sebagai kelompok eksperimen dan siswa kelas VIII-B sebagai kelompok kontrol. Tujuan utama dari penelitian ini adalah untuk menelaah kemampuan komunikasi matematik siswa SMP yang belajar dengan pembelajaran konstruktivisme dalam kelompok kecil dan yang belajar secara biasa, keterkaitan antara kedua kemampuan tersebut serta sikap siswa terhadap pembelajaran dengan model pembelajaran konstruktivisme. Analisis data dilakukan secara kuantitatif dan kualitatif. Analisis kuantitatif dilakukan terhadap data hasil pretes dan postes masing-masing, untuk melihat perbedaan rata-rata antara dua kelompok sampel. Berdasarkan hasil analisis tes akhir diperoleh bahwa kemampuan komunikasi matematik siswa yang belajar dengan model pembelajaran konstruktivisme lebih baik dibandingkan dengan siswa yang belajar dengan pembelajaran biasa. Hasil belajar siswa pada kelompok eksperimen berada pada tingkat baik dan kelompok kontrol hasil belajarnya masih berada pada tingkat kurang. Sedangkan analisis kualitatif diperoleh bahwa aktivitas belajar siswa dalam model pembelajaran konstruktivisme dalam kelompok kecil adalah baik. Siswa dan guru menunjukkan sikap positif terhadap pembelajaran ini. Kata kunci: Model pembelajaran konstruktivis, kemampuan komunikasi matematis